2004
DOI: 10.1111/j.1365-2648.2004.03050.x
|View full text |Cite
|
Sign up to set email alerts
|

Making portfolios work in practice

Abstract: Background. A portfolio captures learning from experience, enables an assessor to measure student learning, acts as a tool for reflective thinking, illustrates critical analytical skills and evidence of self-directed learning and provides a collection of detailed evidence of a person's competence.\ud Aims. This paper reports data on how assessors and nursing students match learning outcomes and/or competencies to their practice and then reconstruct those experiences into the format required by the portfolio do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 15 publications
5
42
0
6
Order By: Relevance
“…Secondly clarity in terms of the aims, guidance and longer term benefits associated with the written evidence may not have been clearly articulated to managers and DMPs. One way that may reduce scepticism is for universities to provide evidence of long term benefits in the context of continuing professional development and revalidation (Scholes et al, 2004). The argument for continuing with portfolio assessment may also be strengthened if there was empirical evidence that demonstrated changes in the student's knowledge and abilities and linking this to patients' outcomes.…”
Section: Ranking Of Assessmentsmentioning
confidence: 99%
“…Secondly clarity in terms of the aims, guidance and longer term benefits associated with the written evidence may not have been clearly articulated to managers and DMPs. One way that may reduce scepticism is for universities to provide evidence of long term benefits in the context of continuing professional development and revalidation (Scholes et al, 2004). The argument for continuing with portfolio assessment may also be strengthened if there was empirical evidence that demonstrated changes in the student's knowledge and abilities and linking this to patients' outcomes.…”
Section: Ranking Of Assessmentsmentioning
confidence: 99%
“…Otro de los aspectos que el profesorado destaca en relación con la utilización del portafolio como instrumento de evaluación es que permite identificar los puntos fuertes y débiles del estudiante, opinión que se contrapone a la de algunos autores que consideran que el portafolio puede ofrecer una imagen distorsionada de sus debilidades y fortalezas [15,16], y a la de otros que resaltan que en ocasiones el estudiante escribe lo que el profesor quiere oír [6].…”
Section: Discussionunclassified
“…Desde el año 1992, en que Glen y Hight [4] publicaron uno de los primeros artículos relativos a su utilización en la formación de enfermeras, los estudios que analizan su utilidad como instrumento de aprendizaje y evaluación en dicha formación se han incrementado de manera progresiva hasta la actualidad. En la literatura existente al respecto se recoge principalmente la opinión de los estudiantes [5][6][7][8], pero sólo se ha encontrado un estudio [9] encaminado a determinar la percepción del profesorado sobre el uso del portafolio. Por esta razón, se ha estimado oportuno describir las experiencias con portafolio que se están llevando a cabo en las escuelas de enfermería españolas y analizar la opinión del profesorado con experiencia en el empleo del portafolio, sobre su utilidad como instrumento de aprendizaje y evaluación.…”
Section: Introductionunclassified
“…[22][23][24][29][30][31]37,38,[41][42][43]45,46 The most extensive use of portfolios comes from the nursing profession. However, this review only found three studies which were in the context of professional practice post-registration.…”
Section: Discussionmentioning
confidence: 99%
“…46 This was part of a larger survey into the use of portfolios in the assessment of competence. The findings suggested that writing in a portfolio was mainly a task to complete and not a reflective tool.…”
Section: Lack Of Benefit To Practicementioning
confidence: 99%